UPAYA PENINGKATAN PEREKONOMIAN MASYARAKAT MELALUI SOSIALISASI PEMBUDIDAYAAN IKAN AIR TAWAR DI DESA KARAMA KECAMATAN KILO KABUPATEN DOMPU - Ramdhani, Muhamad Fajrun; Taradian, Irawani Devi; Irwansyach, Aldy; Asrianti, Yuyun; Yudistira, Hendrawan; Umami, Ruhil; Dewi, Lia Pitriana; Windana, Asvi Prayanka; Aditya, Muhammad Wahyu; Scabra, Andre Rachmat (Jurnal Wicara, 2023)
Karama Village is one of the villages in Kilo District, Dompu Regency, West Nusa Tenggara Province. The domination of the people who live in this village have livelihoods as fishermen, farmers and freshwater fish farming. However, serious problems are found in freshwater fish farming. The low level of public understanding of freshwater fish farming, the high price of feed, and the poor economy of the community are the main obstacles. Therefore, the objective of the Village Community Service Field Work Lecture (KKN-PMD) is Fisheries Development in Karama Village. The method used in implementing the program is carried out through three stages. In the first stage, socializing fish farming to farmer groups and the community. The next stage is to hand over 300 tilapia fingerlings to be distributed in the pond which is the activity area. The last stage, the KKN-PMD team provides feed or fish pellets. Then, guide the fish farmer groups in providing feed or fish pellets according to the dosage. From the results of the activity, it can be concluded that there has been an increase in the knowledge of farmer groups about freshwater fish cultivation, an increase in the skills of farmer groups in providing feed or fish pellets according to the measure and the help of farmer groups in starting cultivation activities with the assistance of providing tilapia fish seeds.